Stepped care versus face-to–face cognitive behavior therapy for panic disorder and social anxiety disorder: Predictors and moderators of outcome. (August 2015) - Haug, Thomas; Nordgreen, Tine; Öst, Lars-Göran; Kvale, Gerd; Tangen, Tone; Andersson, Gerhard; Carlbring, Per; Heiervang, Einar R.; Havik, Odd E.
Abstract: Objective: To investigate predictors and moderators of treatment outcome by comparing immediate face-to-face cognitive behavioral therapy (FtF-CBT) to a Stepped Care treatment model comprising three steps: Psychoeducation, Internet-delivered CBT, and FtF-CBT for panic disorder (PD) and social anxiety disorder (SAD). Method: Patients ( N  = 173) were recruited from nine public mental health out-patient clinics and randomized to immediate FtF-CBT or Stepped Care treatment. Characteristics related to social functioning, impairment from the anxiety disorder, and comorbidity was investigated as predictors and moderators by treatment format and diagnosis in multiple regression analyses. Results: Lower social functioning, higher impairment from the anxiety disorder, and a comorbid cluster C personality disorder were associated with significantly less improvement, particularly among patients with PD. Furthermore, having a comorbid anxiety disorder was associated with a better treatment outcome among patients with PD but not patients with SAD. Patients with a comorbid depression had similar outcomes from the different treatments, but patients without comorbid depression had better outcomes from immediate FtF-CBT compared to guided self-help. Conclusions: In general, the same patient characteristics appear to be associated with the treatment outcome for CBT provided in low- and high-intensity formats when treated in public mental health care clinics. The findings suggest that patients with lower social functioning and higher impairment from their anxiety disorder benefit less from these treatments and may require more adapted and extensive treatment. ClinicalTrials.gov: Identifier: NCT00619138 . Highlights: We investigate predictors and moderators in face-to-face CBT versus stepped care. The study is conducted in a naturalistic setting. Low social functioning and higher impairment predicts a worse treatment outcome. Presence of a cluster C personality disorder predicts a worse treatment outcome. The same factors are associated with the outcome from different formats of CBT.